2016
DOI: 10.1093/femspd/ftw041
|View full text |Cite
|
Sign up to set email alerts
|

SLA-PGN-primed dendritic cell-based vaccination induces Th17-mediated protective immunity against experimental visceral leishmaniasis: a crucial role of PKCβ

Abstract: Emergence of drug resistance during visceral leishmaniasis (VL) is a major obstacle imposed during successful therapy. An effective vaccine strategy against this disease is therefore necessary. Our present study exploited the SLA (soluble leishmanial antigen) and PGN (peptidoglycan) stimulated bone marrow-derived dendritic cells (DCs) as a suitable vaccine candidate during experimental VL. SLA-PGN-stimulated DCs showed a significant decrease in hepatic and splenic parasite burden, which were associated with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Similarly, in a recent study, we showed an increase in IL-17-secreting CD4 T cells in the PBMCs isolated from healed VL individuals after stimulation with LdCen −/− parasites ex vivo (65). In another study using Leishmania Ag-stimulated DCs as a vaccine, induction of IL-6, IL-23, and TGF-β expression was observed, which in turn resulted in IL-17-producing CD4 T cells leading to host protection against experimental VL (26). Thus, both experimental animal studies and observations from clinical studies in endemic areas support a strong role for Th17 in protection against VL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a recent study, we showed an increase in IL-17-secreting CD4 T cells in the PBMCs isolated from healed VL individuals after stimulation with LdCen −/− parasites ex vivo (65). In another study using Leishmania Ag-stimulated DCs as a vaccine, induction of IL-6, IL-23, and TGF-β expression was observed, which in turn resulted in IL-17-producing CD4 T cells leading to host protection against experimental VL (26). Thus, both experimental animal studies and observations from clinical studies in endemic areas support a strong role for Th17 in protection against VL.…”
Section: Discussionmentioning
confidence: 99%
“…Successful therapy of VL with different immune modulatory molecules has been shown to induce Th1 cytokines, along with IL-17, IL-22, and IL-23 (2325). A recent report demonstrated that leishmanial Ag-stimulated DCs exhibit a potent anti-leishmanial role by the induction of proinflammatory cytokines and generation of Th17 cells during experimental VL infection (26). In contrast, in cutaneous leishmaniasis caused by L. major it has been shown that Th17 cells influence disease progression via regulation of tissue-destructive neutrophil recruitment at the lesion site (27).…”
mentioning
confidence: 99%
“…DCs can be pulsed with parasite extracts alone ( Ahuja et al, 1999 ; Carrion et al, 2008 ; Majumder et al, 2012 ; Masic et al, 2012 ), combined with adjuvants such as CpG-ODN ( Carrion et al, 2008 ; Agallou et al, 2011 , 2012 ; Majumder et al, 2012 ; Masic et al, 2012 ) or peptidoglycan (ligand of the TLR-2) ( Jawed et al, 2016 ) or in DCs engineered to secrete IL-12 ( Ahuja et al, 1999 ). These different treatments boost their immunogenicity in murine models ( Ahuja et al, 1999 ; Majumder et al, 2012 ; Jawed et al, 2016 ), dampening IL-10 responses associated to parasite infection ( Schwarz et al, 2013 ), and decreasing the tissue damage induced by the inflammatory response after infective challenge in vaccinated animals ( Masic et al, 2012 ). Due to the high cost of these procedures, an alternative to the use of DCs primed with recombinant parasite proteins in humans will be to target Leishmania proteins to DCs by constructing recombinant chimeras, such as recombinant antibodies recognizing DC-specific receptors and containing leishmanial proteins.…”
Section: Fighting Back Immune Evasion By Vaccinationmentioning
confidence: 99%
“…On the other hand, DC vaccines have also been used to improve the immune response to the Th17 profile against Leishmania spp. infection ( 77 ). Application of DCs in IT against M. leprae has not been explored despite the potential for the stimulation of an efficient antibacterial immunity.…”
Section: Antigen-presenting Cellsmentioning
confidence: 99%
“…Application of DCs in IT against M. leprae has not been explored despite the potential for the stimulation of an efficient antibacterial immunity. In other disease, the results indicate that DC-based IT might be more effective in combination with conventional treatments because the association should modulate the immune system in a way that helps the host control or eliminate pathogens ( 68 , 77 , 78 ). Therefore, exploring strategies to shift the immune response to Th1 might achieve better outcomes in leprosy treatment, leading to reduced expression of M. leprae virulence factors, such as LAM, PGL-I, and lipid metabolism ( 9 , 10 ).…”
Section: Antigen-presenting Cellsmentioning
confidence: 99%